If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 6 = 2a + 20 Reorder the terms: 6 + 5a = 2a + 20 Reorder the terms: 6 + 5a = 20 + 2a Solving 6 + 5a = 20 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. 6 + 5a + -2a = 20 + 2a + -2a Combine like terms: 5a + -2a = 3a 6 + 3a = 20 + 2a + -2a Combine like terms: 2a + -2a = 0 6 + 3a = 20 + 0 6 + 3a = 20 Add '-6' to each side of the equation. 6 + -6 + 3a = 20 + -6 Combine like terms: 6 + -6 = 0 0 + 3a = 20 + -6 3a = 20 + -6 Combine like terms: 20 + -6 = 14 3a = 14 Divide each side by '3'. a = 4.666666667 Simplifying a = 4.666666667
| 3x^2+18x-27=0 | | x^2+23+60=0 | | 2x^2-72=0 | | 8x+18=58 | | x+7=19+2x | | 7+3x=23+x | | 7x-19=-2 | | 6x+38=74 | | 8x^2+5x-6=0 | | 6x-(2x+5)=19 | | -4(7-2s)=11 | | 6x+31=8x+13 | | 14-9x=3x-70 | | 6x+1=26-2x | | 10x+5y=-15 | | -4(2x-10)+3=-10 | | 7(6x-3)=29 | | a^2+7ab+10b^2= | | b^3+49b= | | 10-2w=-12 | | 10-2w=12 | | 7x^2+2x-9=0 | | 2x+13=9x-8 | | 9a+4a=8a | | 4x-1=11x-42 | | 2x+22=10x-42 | | -10x+15=5x-30 | | -7(t-3)+4t=-3(-7+t) | | (-6)-5= | | (7)(-4)= | | 2x+5=7x-20 | | 2q-4+8q=7q-8+3q |